YouTube sebagai Media Teknologi Informasi dan Komunikasi dalam Konteks Hasil Pembelajaran Praktik Instrumen Violin Prodi Pendidikan Musik Institut Seni Indonesia Yogyakarta - Sagaf Faozata Adzkia (Institut Seni Indonesia Denpasar, 2021)
Purpose: This article describes the creation of youtube video content as a result of learning violin instrument practice of the ISI Yogyakarta Fakultas Seni Pertunjukan Music Education Study Program, and analyzes the role of youtube as a medium for information and communication technology in the community in the context of learning outcomes of the violin instrument practice in the Music Education Study Program of FSP ISI Yogyakarta. Research methods: This study uses an interdisciplinary approach and qualitative research methods. Results and discussion: The answer to the first problem regarding the making of youtube video content as a result of learning the violin instrument practice course includes the preparation of a video design, consultation with the head of study program regarding ideas, preparing human resources/talent, carrying out recording, carrying out video editing, and posting videos of learning results of the violin instrument practice to youtube . In the second problem, the research results obtained that the recording of learning outcomes of the violin instrument practice in the ISI Yogyakarta Music Education Study Program is a form of achievement of learning targets for lecturers and students. Implication: Video recording of learning outcomes is an information on academic identity through the mechanism of processing recording works, storing audio-visual data on learning outcomes, and disseminating and presenting information on learning processes and outcomes institutionally.